Efeito da associação de furosemida e fenilbutazona sobre variáveis hidroeletrolíticas de cavalos antes e após a corrida - Camargos, A. S. [UNESP]; Costa, A. P. D.; Carvalho, C. B.; Guidi, R. C.; Quirino, C. R.; Batista, A. M. B.; Machado, J. A. (Arquivo Brasileiro Medicina Veterinaria Zootecnia, 2011)
The objective of this study was to verify the effects of furosemide and phenylbutazone association on fluid and electrolyte balance characteristics of horses before and after a race. Nineteen horses were divided into three groups according to treatment protocols. The first group (five animals - control) was not medicated. A second group (seven animals) was treated with furosemide (1mg/kg, intramuscular up to four hours before the race). A third group (seven animals) received furosemide (1mg/kg) and phenylbutazone (4.4 mg/kg), both intramuscular, up to four hours before race. Blood samples were collected before, immediately after and two hours after a race to evaluate the plasma osmolality and sodium, potassium and chloride concentrations. The use of furosemide and furosemide plus phenylbutazone up to four hours before the race altered (P<0.05) the plasma osmolality but did not change (P>0.05) the sodium, potassium and chloride concentrations. It was not possible to determine an antagonist effect of phenylbutazone on furosemide, based on fluid and electrolyte balance. Due to the high intensity exercise, the increase in plasma osmolality and potassium concentration was attributed to the race effect.
The effect of furosemide and phenylbutazone association on the fluid and electrolyte characteristics of horses before and after a race
Keywords: athletic horses; electrolytes; plasma osmolality; diuretic